RELATIONSHIP BETWEEN THE CLASSICAL NUMERICAL RANGE AND ESSENTIAL NUMERICAL RANGES - Owego, D. O.; Okelo, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
In this paper we discuss the relationships between the numerical range and the essential numerical range. We prove two theorems in this paper that show how the numerical range and the essential numerical range are related. Finally, we discuss the roles of the essential numerical range in operator theory.